Pengaruh Hedonic Shopping Motivation Dan Penggunaan Paylater Terhadap Impulse Buying Pada Pengguna E- Commerce Shopee (Studi Kasus Generasi Z Di Kota Jambi) - M. Gunawan (Universitas 45 Surabaya, 2024)
The current internet users are predominantly dominated by Generation Z, attributed to their openness in embracing various technological changes, thereby making them more receptive to innovations and technological advancements. This research was conducted to obtain an overview of Hedonic Shopping Motivation and the Use of Paylater on Impulse Buying among Generation Z Shopee e-commerce users in Jambi City, as well as to determine the extent of the influence of each independent variable on the dependent variable both simultaneously and partially. The data collection technique employed was an online questionnaire distributed via Google Forms. The sample used in the study consisted of 100 respondents selected through purposive sampling method. The analytical method used was multiple regression. The research findings indicate that there is an influence of Hedonic Shopping Motivation and the Use of Paylater as independent variables on Impulse Buying as the dependent variable. The Hedonic Shopping Motivation variable was found to have the greatest influence at 48.49 percent.